Probiotics in irritable bowel syndrome – is the quest for the right strain over? Rapid review of existing guidelines and recommendations - Marlicz, Wojciech; Skonieczna-Żydecka, Karolina; Krynicka, Patrycja; Łoniewski, Igor; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Irritable bowel syndrome (IBS) – functional gastrointestinal disorder (FGIDs) and disorder of gut-brain interaction (DGBIs) – has emerged as an important medical problem with an impact on health care systems, affecting patients’ quality of life. The management of IBS consists of pharmacological and non-pharmacological treatments; however, the data of their long-term efficacy are scarce. Modulation of gastrointestinal microbiota, by means of probiotics and prebiotics, is often sought and advertised as a popular treatment modality in IBS. Faecal microbiota transplantation (FMT) awaits recommendations for IBS treatment and requires more methodological assessments. To date, numerous guidelines and recommendations have been published on the role of probiotics in IBS. Because no probiotic claim for probiotics in foods has yet been granted by the European Food and Safety Authority (EFSA), medical practitioners still recommend probiotics on the basis of available literature and recommendations released by independent health authorities. We aimed to summarize published formal recommendations and guidelines regarding the clinical effectiveness of available probiotic strains and conduct a random-effects meta-analysis of outcomes for which ≥ 2 studies contributed data on the same probiotic strain recommended to adults with IBS. Based on available and most recent guidelines, we report that probiotics, as a group, may be an effective treatment for global symptoms and abdominal pain in IBS, with the strongest effect for genus Lactobacillus. Our current and updated meta-analysis is in line with several reports documenting significant effects of Lactobacillus plantarum (Lp299v) in reducing the risk of global symptoms and their persistence, which could assist clinicians in making the choice for the right probiotic strain in IBS patients.